FIB-SEM and ToF-SIMS Analysis of High-Temperature PEM Fuel Cell Electrodes - Braig, Michael; Deissler, Niklas H.; Lüdeking, Ildiko; Regnet, Fabian; Bevilacqua, Nico; Zeis, Roswitha (Advanced Materials Interfaces, 2023)
The phosphoric acid (PA) distribution in the electrodes is a crucial factor for the performance of high-temperature polymer electrolyte fuel cells (HT-PEM FCs). Therefore, understanding and optimizing the electrolyte distribution is vital to maximizing power output and achieving low degradation. Although challenging, tracking the PA in nanometer-sized pores is essential because most active sites in the commonly used carbon black-supported catalysts are located in pores below 1 µm. For this study, a cell is operated at 200 mA cm−2 for 5 days. After this break-in period, the cathode is separated from the membrane electrode assembly and subsequently investigated by cryogenic focused ion beam scanning electron microscopy (cryo FIB-SEM) coupled with energy-dispersive X-ray spectroscopy (EDX) and time-of-flight secondary ion mass spectrometry (ToF-SIMS). PA is located on the surface and in the bulk of the cathode catalyst layer. In addition, the PA distribution can be successfully linked to the gas diffusion electrode morphology and the binder distribution. The PA preferably invades nanometer-sized pores and is uniformly distributed in the catalyst layer.
CRIS-Team Scopus Importer:2023-08-01
Keywords: focused ion beam scanning electron microscopy (FIB-SEM); high-temperature polymer electrolyte membrane fuel cells (HT-PEM FC); phosphoric acid distribution; polybenzimidazole (PBI); time-of-flight secondary ion mass spectrometry (ToF-SIMS)